STAT3-Ser/Hes3 signaling: a new molecular component of the neuroendocrine system? - Nikolakopoulou, P.; Poser, S.W.; Masjkur, J.; Fernandez Rubin de Celis, M.; Toutouna, L.; Andoniadou, C.L.; McKay, R.D.; Chrousos, G.; Ehrhart-Bornstein, M.; Bornstein, S.R.; Androutsellis-Theotokis, A. (Georg Thieme Verlag, 2016)
The endocrine system involves communication among different tissues in distinct organs, including the pancreas and components of the Hypothalamic- Pituitary-Adrenal Axis. The molecular mechanisms underlying these complex interactions are a subject of intense study as they may hold clues for the progression and treatment of a variety of metabolic and degenerative diseases. A plethora of signaling pathways, activated by hormones and other endocrine factors have been implicated in this communication. Recent advances in the stem cell field introduce a new level of complexity: adult progenitor cells appear to utilize distinct signaling pathways than the more mature cells in the tissue they co-reside. It is therefore important to elucidate the signal transduction requirements of adult progenitor cells in addition to those of mature cells. Recent evidence suggests that a common non-canonical signaling pathway regulates adult progenitors in several different tissues, rendering it as a potentially valuable starting point to explore their biology. The STAT3- Ser/Hes3 Signaling Axis was first identified as a major regulator of neural stem cells and, subsequently, cancer stem cells. In the endocrine/neuroendocrine system, this pathway operates on several levels, regulating other types of plastic cells: (a) it regulates pancreatic islet cell function and insulin release; (b) insulin in turn activates the pathway in broadly distributed neural progenitors and possibly also hypothalamic tanycytes, cells with important roles in the control of the adrenal gland; (c) adrenal progenitors themselves operate this pathway. The STAT3-Ser/Hes3 Signaling Axis therefore deserves additional research in the context of endocrinology.